Spin-outs from Universities: Strategy, Financing, Monitoring and Incubation Models - Wright, Mike; Lockett, Andy (Senate Hall, 2004)
Spin-outs of ventures from universities are growing in importance yet their process is little understood. This paper reviews evidence from the spin-out and university level relating to four key research questions: What mechanisms are in place to facilitate the spinning-out of new technologies into companies? What financial resources are made available by universities and outsiders to facilitate spin-out companies and at what stage? What mechanisms and processes are in place to monitor spin-out companies once they have been established? How effective are these systems and processes from the viewpoint of the participants and in terms of spin-out company success. Implications for practice and areas for further research are identified.
Keywords: universities|technology transfer|entrepreneurship|venture capital|spin-offs|and incubators